How we remember the emotional intensity of past musical experiences - Schäfer, Thomas; Zimmermann, Doreen; Sedlmeier, Peter (Frontiers in Psychology, 2014)
Listening to music usually elicits emotions that can vary considerably in their intensity over the course of listening. Yet, after listening to a piece of music, people are easily able to evaluate the music’s overall emotional intensity. There are two different hypotheses about how affective experiences are temporally processed and integrated: (1) all moments’ intensities are integrated, resulting in an averaged value; (2) the overall evaluation is built from specific single moments, such as the moments of highest emotional intensity (peaks), the end, or a combination of these. Here we investigated what listeners do when building an overall evaluation of a musical experience. Participants listened to unknown songs and provided moment-to-moment ratings of experienced intensity of emotions. Subsequently, they evaluated the overall emotional intensity of each song. Results indicate that participants’ evaluations were predominantly influenced by their average impression but that, in addition, the peaks and end emotional intensities contributed substantially. These results indicate that both types of processes play a role: All moments are integrated into an averaged value but single moments might be assigned a higher value in the calculation of this average.